Ultrasound Parameters Changes after Pyeloplasty in Ureteropelvic Junction Obstruction: 6-Month Follow-Up - Mohajerzadeh, Leily; Nozarnezhad, Shahram; Karimi, Sajede; Faghihi, Amirhossein; Sarafi, Mehdi; Ebrahimi Saraj, Gholamreza; Niroomand, Behnaz (Iranian Journal of Pediatric Surgery, 2023)
Background: Ureteropelvic junction obstruction(UPJO) is one of the most common anomalies in children. The gold standard method for follow-up of these patients after pyeloplasty is a nuclear scan, but due to its high cost and limited access, it has recently been replaced with ultrasound. In this study, we want to assess ultrasound parameter changes after pyeloplasty. Methods: In this cross-sectional analytical study, 124 patients from 2006 to 2012 who had undergone open pyeloplasty were enrolled. They were evaluated with ultrasound and nuclear scans before, 3, and 6 months after surgery. We analogized the results of these two methods and described the modifications in ultrasound parameters. Results: Of all 124 patients with a median age of 30 months, according to nuclear scan results, kidney functions have improved by 96.77%. The average AP(anteroposterior) diameter of kidneys before, 3, and 6 months after surgery were 34.28 mm, 18 mm, and 15.19 mm respectively. In patients with successful surgery; PI (percentage improvement) of AP was above 15% after 3 months and above 26% after 6 months, thickness of the cortex raised at least 10 percent, and a reduction of at least 16% and 18% was seen in pelvic/cortex ratio in 3, and 6 months respectively. Conclusions: After pyeloplasty, a reduction in AP diameter, PI of AP, pelvic/cortex ratio, and an expansion in thickness of the cortex have been seen. Ultrasound in 3 months has high sensitivity but low specificity, and in 6 months have high sensitivity and specificity.